2015
DOI: 10.3109/15513815.2015.1087607
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Membranous Nephropathy and IgA Nephropathy

Abstract: We herein present a case of a 14-year-old boy with the histological features of coexisting membranous nephropathy (MN) and IgA nephropathy (IgAN). Asymptomatic hematuria/proteinuria was initially detected in school urinary screening, with treatments including oral corticosteroids leading to complete remission. Cases of coexisting MN and IgAN are very rare among the pediatric population; however, the overlap of these two nephropathies does not always imply a deleterious clinical outcome in pediatric cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Similarly, Nishida et al . reported a pediatric case of coexisting MN and IgAN and suggested that overlapping MN and IgAN might not lead to deleterious outcomes 21 . The physiological and cellular mechanisms underlying the overlapping IMN and IgAN-associated increase in disease remission remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nishida et al . reported a pediatric case of coexisting MN and IgAN and suggested that overlapping MN and IgAN might not lead to deleterious outcomes 21 . The physiological and cellular mechanisms underlying the overlapping IMN and IgAN-associated increase in disease remission remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Existe escasa información sobre la GC, especialmente, en pediatría. 1,2,4 Cheong et al encontraron, en 294 niños, 9 casos de GC (3,1%). 1 En adultos, Monga y colaboradores hallaron 9 casos de GC entre 1715 biopsias de pacientes adultos (0,5%), 5 y Bertani, 7 entre 105 biopsias renales (7%).…”
Section: Discussionunclassified
“…1,13,14 No hay evidencia de que la presencia de GC empeore el pronóstico renal de los pacientes más allá de lo que se espera para cada entidad aislada. 2,12,15 Se desconoce si la aparición de un segunda glomerulopatía es coincidencia o se trata de una entidad glomerular única diferente con un mecanismo patogénico común. 2,12 En conclusión, las GC son infrecuentes en los niños y su presentación es muy variable, por lo que es necesaria la biopsia renal para su diagnóstico definitivo.…”
Section: Discussionunclassified
“…In this report, SLE and T1DM co-exist more often than expected based on the prevalence of both diseases. Several case reports describe different overlapping auto-immune diseases that affect the kidney, such as MN and IgA nephropathy 29 or MN and further extra-renal autoimmune diseases such as colitis ulcerosa) 30 . More detailed and better powered studies focusing on SNP associations across sub-types of different autoimmune diseases are required to address these important questions in more detail.…”
Section: Discussionmentioning
confidence: 99%